Strategi Komunikasi Public Relations dalam Meningkatkan Kualitas Pelayanan pada Penghuni Apartemen Studi Kasus Apartemen Green Bay Pluit - Yunita Ratmelia; Dani Setiadarma (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study aims to analyze the Public Relations communication strategy implemented by the management of Green Bay Pluit Apartment in improving service quality and shaping residents’ image perception. The research adopts a constructivist paradigm using a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive model and the Strategic Planning for Public Relations framework. The findings reveal that the communication strategy was conducted systematically through situation analysis, planning, implementation, and evaluation stages. Elevator malfunction emerged as the dominant issue affecting residents’ service experience. The utilization of WhatsApp Group as the primary communication channel enabled fast, documented, and dialogic information delivery. Empathetic, transparent, and solution-oriented messaging patterns contributed to maintaining residents’ trust despite operational technical constraints. Periodic evaluations through briefings and satisfaction surveys indicate gradual improvement in the perceived quality of management communication. The study confirms that in vertical housing management, the effectiveness of Public Relations communication strategy depends not only on message delivery but also on the consistency of technical actions accompanying it. Responsive and structured communication serves as a fundamental element in sustaining a positive organizational image